2014
DOI: 10.1097/icl.0b013e3182a70ef7
|View full text |Cite
|
Sign up to set email alerts
|

Review of Complications Associated With Contact Lenses From Unregulated Sources of Supply

Abstract: There are various reasons to presume that the unregulated supply of CLs might result in the use of inappropriate lenses, increase the risk of poorer lens hygiene, and militate against the prompt treatment of any consequent complications. There is some indication that the introduction of regulations to control the supply of plano CLs has alleviated the level of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…Another observation from Young et al described a French case–control study of patients with microbial keratitis contracted from contact lens wear. In this study, it was shown that decorative contact lens wearers were 85 times more likely to have acquired their contact lenses from an unregulated source when compared to noncosmetic contact lens users .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another observation from Young et al described a French case–control study of patients with microbial keratitis contracted from contact lens wear. In this study, it was shown that decorative contact lens wearers were 85 times more likely to have acquired their contact lenses from an unregulated source when compared to noncosmetic contact lens users .…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fact that the FDA requires prescriptions for all contact lens products, each year thousands of consumers obtain contact lenses through channels which evade regulatory authority and may not meet industry standards for safety. Also, consumers who bypass the counsel of an eye‐care practitioner significantly increase their risk of ocular infections such as microbial keratitis . Sauer et al reported that the risk of microbial keratitis for decorative contact lens is 16.5 times greater than normal contact lenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated prevalence varies from 6.3 to 710 per 100,000 (1). The high incidence is due not only to poor hygiene standards and a greater risk of infection in developing countries, but also to the widespread use of contact lenses with associated complications in industrial nations (3,4). The two primary gram-positive and gram-negative bacterial strains responsible for causing bacterial keratitis are Staphylococcus aureus and Pseudomonas aeruginosa (1).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to low hygiene standards and water quality with a greater risk of infection in poor countries. In addition, the widespread use of contact lenses and associated complications in wealthier countries contributes to severe keratitis (2,3). Staphylococcus aureus and Pseudomonas aeruginosa are two predominant gram-positive and gram-negative bacterial strains responsible for causing this disease (1,4,5).…”
Section: Introductionmentioning
confidence: 99%